Association of periconceptional or pregnancy exposure of HPV vaccination and adverse pregnancy outcomes: a systematic review and meta-analysis with trial sequential analysis - Yan, Xiaoli; Li, Hongyu; Song, Bin; Huang, Ge; Chang, Qing; Wang, Dan; Yan, Ping (Frontiers in Pharmacology, 2023)
Objective: To evaluate whether periconceptional or pregnancy exposure of human papillomavirus (HPV) vaccination would increase the risk of adverse pregnancy outcomes. Methods: The PubMed, Web of Science, Embase, the Cochrane Library of clinical trials were searched from inception to March 2023. We computed relative risk (RR) and 95% confidence intervals (CIs) and prediction intervals (PIs) regarding the association between HPV vaccination in periconceptional period or during pregnancy and the risks of adverse pregnancy outcomes by using R software Version 4.1.2 and STATA Version 12.0. A trial sequential analysis (TSA) was performed with TSA v0.9.5.10 Beta software. Results: Four randomized controlled trials (RCTs) and eight cohort studies were included in this meta-analysis. Analysis of RCTs showed that HPV vaccination in periconceptional period or during pregnancy did not increase the risks of spontaneous abortion (RR = 1.152, 95% CI: 0.909–1.460, 95% PI: 0.442–3.000), birth defects (RR = 1.171, 95% CI: 0.802–1.709, 95% PI: 0.320–4.342), stillbirth (RR = 1.053, 95% CI: 0.616–1.800, 95% PI: 0.318–3.540), preterm birth (RR = 0.940, 95% CI: 0.670–1.318) and ectopic pregnancy (RR = 0.807, 95% CI: 0.353–1.842, 95% PI: 0.128–5.335). In cohort studies, periconceptional or pregnancy exposures of HPV vaccine were not associated with the increased risk of spontaneous abortion (RR = 0.987, 95% CI: 0.854–1.140, 95% PI: 0.652–1.493), birth defects (RR = 0.960, 95% CI: 0.697–1.322, 95% PI: 0.371–2.480), stillbirth (RR = 1.033, 95% CI: 0.651–1.639, 95% PI: 0.052–21.064), small size for gestational age (SGA) (RR = 0.971, 95% CI: 0.873–1.081, 95% PI: 0.657–1.462) and preterm birth (RR = 0.977, 95% CI: 0.874–1.092, 95% PI: 0.651–1.444). Conclusion: HPV vaccine exposures in periconceptional period or during pregnancy did not increase the risks of adverse pregnancy outcomes, including spontaneous abortion, birth defects, stillbirth, SGA, preterm birth and ectopic pregnancy. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/, identifier CRD42023399777.